(untitled) (Acque Sotterranee - Italian Journal of Groundwater, 2019)
The characterization of the river boundary condition in finite difference numerical models based on MODFLOW requires the quantification of a set of parameters, some of them usually difficult to define. A methodology is presented based on the digital elevation model (DEM) and the river network, to characterize two of these parameters: the stage of the river and the length of the river in each model cell. Suggestions are presented for the other parameters such as the riverbed bottom elevation and the width of the river to be calculated as a function of the river stage, and the riverbed thickness and hydraulic conductivity. The part of the methodology depending on the DEM is explained and demonstrated using a GIS environment with reference to the GIS tools needed to produce the main steps. This methodology produces more representative values of the river stage parameter if at least 9 DEM cells per model cell are used. This methodology allows a first approximation, at a regional scale, for the characterization of the river boundary condition in numerical modelling.